Evaluation of a combined ridge expansion technique with simultaneous implant placement in narrow mandibular ridges - Melek, L.N.F. (Journal of Osseointegration, 2023)
Background Implant placement in the posterior mandible is sometimes problematic, due to loss of horizontal bone width after extraction of posterior teeth. Aim of the study Evaluation of dental implants placed simultaneously with piezotomed ridge splitting and osseodensification in the posterior mandible. Methods Eight patients with long span narrow edentulous ridge in the posterior mandible underwent piezotomed ridge splitting and osseodensification with simultaneous implant placement. Implant stability was assessed. Also, bone width gained, and bone density were measured around the dental implants using cone beam computed tomography. Results The mean bone density and ridge width have increased significantly after ridge splitting and ossseodensification. The mean ISQ value at time of implant placement was 68.43 ± 5.40. At 4 weeks, it was 66.62 ± 5.79 and at 3 months, it was 70.93 ± 4.67. The difference was statistically significant. Conclusion The combined ridge expansion technique using piezotomed ridge splitting and osseodensification is an effective method for simultaneous implant placement in the narrow posterior mandible, evidenced by increase of bone density, ridge width and good implant stability.